The Role of Islamic Religious Teachers in Shaping Students’ Digital Ethics in the Social Media Era - U Abdullah Mu'min; Budi Munawar Khutomi; M Renaldy Fadillah (Jurnal al-Thullab, 2026)
This study examines the role of Islamic Religious Education teachers in shaping students’ digital ethics in the social media era at SMAN 1 Palabuhanratu. Using a qualitative case study design, this research involved five participants, including two Islamic Religious Education teachers, one school principal, and two students selected through purposive sampling. Data were collected through semi-structured interviews and document analysis and analyzed using thematic analysis. The findings reveal that teachers play central roles as educators, moral guides, and facilitators in developing students’ digital ethics. These roles are implemented through contextual learning strategies, such as group discussions, case-based learning, and reflective assignments that connect Islamic values with students’ digital experiences. The study also identifies key challenges, including limited student awareness of digital ethics, exposure to negative online content, and inconsistent parental supervision. To address these challenges, teachers actively foster collaboration with parents and link ethical learning in school with students’ social environments. This study highlights the active and contextual role of teachers in shaping students’ digital ethics and underscores the importance of integrating moral and religious values into digital learning practices across educational settings.